Flexible Approach for Data Mining using Grid based Computing Concepts (International Journal of Engineering and Computer Science, 2017)
Now days, in the field of life sciences and business, knowledge discovery has become a common task in both for the growing amount of data being gathered and for the complexity of the analysis that need to be performed on it. Due to some unique characteristics of today’s data sources, such as their heterogeneity, high dimensionality, distributed nature and large volume. Distribution of data and computation allows increasing trend towards decentralized business organizations; distribution of users, software, and hardware systems magnifies the need for more advanced and flexible approaches and solutions. Here we present the state of the art about the major data mining techniques, systems and approaches. This paper discusses how distributed and Grid computing can be used to support distributed data mining. In particular, a distinction is made between distributed and Grid-based data mining methods.